Understanding the Impact of the Counter-Terror Agenda on Humanitarian Action - Francesco Bruno (Otoritas : Jurnal Ilmu Pemerintahan, 2017)
The paper reflects on the impact of the counter-terror agenda on humanitarian actions. It explores the socio-political and legal implications and constraints that Non-Governmental Organisations incur when managing humanitarian projects in critical environments such as Somalia where, an important famine stroke in 2011 as consequence of the counter-terror agenda, insecurity and politicization. In the case of Somalia, Al-Shabaab, a group well-known to the international authority as affiliated to Al-Qaeda was in charge of the area in which the famine stroke. The dilemma to consider in this paper is  paper is related to the binomial situation between the people in need and the counter-terrorism strategy against Al-Shabaab.The paper outlines three issues that the humanitarian actors incur, namely structural, operational and of internal nature. These three issues undermines the relationship between the Humanitarian actors and the donors as well as between humanitarian actors and their recipients. At the end, the relationship continues to be highly controversial.